Effects of Betaine on Protein Deposition in Growing Cattle with Modulated Methyl Group Status - M. S. Grant; J. M. Marsh; K. J. Hazlewood; M. D. Miesner; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:This study was conducted to evaluate effects of guanidinoacetic acid and creatine supplementation in the presence or absence of supplemental betaine on lean tissue growth in growing cattle. Study Description:Seven ruminally cannulated Holstein steers (417 lb) were used in an experiment where each steer received each of six treatments. The first treatment set was conducted via abomasal infusion of a saline solution (control), 15 g/day guanidinoacetic acid (GAA), or 16.8 g/day creatine, and the second set was conducted via abomasal infusion of 0 or 5.6 g/day betaine; all treatment combinations were represented. Complete collection of urine and feces was used to determine nitrogen retention as a measure of protein deposition. Steers were limit-fed a corn-based diet similar to that of a production-type setting. Bottom line:Supplementing 5.6 g/day betaine increased lean tissue growth in growing steers fed corn-based diets.
Keywords: betaine; guanidinoacetic acid; growing cattle